Synthesis and Characterization of Polymeric Complex of Cu(II) with Cyclodichloro Phosphazene - SHARMA, H.K. (Asian Journal of Chemistry, 2010)
(PNCl2)3 is used as ligand to prepare its complex with CuCl2. To Know the nature and composition of the complex its IR, UV and EPR spectra are analyzed alongwith quantitative estimation and molecular weight determination. The various parameters energy gap (ΔE), μeff, gII, g⊥, χA, A/B and oscillation strength (f) have also been computed. It is concluded from IR, UV and EPR spectra that the complex is a semiconductor polymer having the composition [(P3N3Cl5)+ (CuCl3-)]3.